Strategy Formulation and Recommendation for Grain Healthy Food and Beverages. - Nugroho, Martin Priyo; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2015)
Abstract.Organic food markets are growing in Jakarta. Therefore, many new organic food business arise. One of them is Grain Healthy Food and Beverages (Grain), which has specialty in healthy nut products. As a start-up business, they face problems. Under the uncertain business conditions, it is difficult to stand out in the market, not to mention the limited capital and resources. The low sales and lack of marketing strategy have resulted in low profit before tax. The objective of this paper is to develop, design and implement the right business strategy for Grain. PEST analysis (Political Economic Social Technological) and Porter’s five forces analysis are used to analyze the external business environment. Whilst internal business environment is analyzed using business model assessment and corporate resources analysis - resource based view. Then those input factors are processed by using IFAS and EFAS matrix (Internal and External Assessment Summary). The Grand Strategy Matrix and Quantitative Strategy Matrix are used to find out the proper company strategy formulation. Porter’s Generic Competitive Strategies is used to find out the business strategy. And TOWS (Threat Opportunities, Weaknesses and Strengths) Matrix are used to find out the functional strategies. All the strategy formulation are summarized in a five-year-long-range plan of road map. To help the business owners visualize the strategies, the paper also suggests new business model canvas on how the company should deliver, create and capture the value. Then the recommended solutions are described in the implementation plan; which includes programs, budget, and timeline.Keywords: Start-up, strategy, entrepreneurship